Susceptibility of frogs to chytridiomycosis correlates with increased levels of immunomodulatory serotonin in the skin. (1st August 2019) - Claytor, Sieara C.; Gummer, Joel P.A.; Grogan, Laura F.; Skerratt, Lee F.; Webb, Rebecca J.; Brannelly, Laura A.; Berger, Lee; Roberts, Alexandra A.
Abstract: Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is a skin disease responsible for the global decline of amphibians. Frog species and populations can vary in susceptibility, but this phenomenon remains poorly understood. Here, we investigated serotonin in the skin of infected and uninfected frogs. In more susceptible frog populations, skin serotonin rose with increasing infection intensity, but decreased in later stages of the disease. The more resistant population maintained a basal level of skin serotonin. Serotonin inhibited both Bd sporangial growth and Jurkat lymphocyte proliferation in vitro. However, serotonin accumulates in skin granular glands, and this compartmentalisation may prevent inhibition of Bd growth in vivo. We suggest that skin serotonin increases in susceptible frogs due to pathogen excretion of precursor tryptophan, but that resistant frogs are able to control the levels of serotonin. Overall, the immunosuppressive effects of serotonin may contribute to the susceptibility of frogs to chytridiomycosis.